Characterization of liposomal carriers for the trans-scleral transport of Ranibizumab - Joseph, Rini Rachel (2018)
Age-related macular degeneration (AMD) is a leading cause of blindness in the modern world. The standard treatment regimen for neovascular AMD is the monthly/bimonthly intravitreal injection of anti-VEGF agents such as ranibizumab or aflibercept. However, these repeated invasive injections can lead to sight-threatening complications. Sustained delivery by encapsulation of the drug in carriers is a way to reduce the frequency of these injections. Liposomes are biocompatible, non-toxic vesicular nanocarriers, which can be used to encapsulate therapeutic agents to provide sustained release. The protein encapsulation was performed by a modified dehydration-rehydration (DRV) method. The liposomes formed were characterized for size, zeta potential, encapsulation efficiency, stability, in vitro release, and ex vivo release profiles. In addition, the localization of the liposomes themselves was studied ex vivo. Entrapment-efficiency of ranibizumab into 100-nm liposomes varied from 14.7 to 57.0%. Negatively-charged liposomes prepared from DPPC-DPPG were found to have the slowest release with a low initial burst release compared to the rest of liposomal formulations. The ex vivo protein release was found to slower than the in vitro protein release for all samples. In conclusion, the DPPC-DPPG liposomes significantly improved the encapsulation and release profile of ranibizumab.